Estimation and comparison of benefits due to feeding hay and silage during the dry season on commercial dual-purpose cattle production systems in Honduras and Costa Rica - Schoonhoven, Aart van; Holmann, Federico J.; Argel M., Pedro J.; Pérez, E.; Ordoñez, J.C.; Chaves, J. (2006)
Smallholders with dual-purpose cattle production systems in most Central America experience a shortage of forages during the dry season (4-8 month. As a result, substantially lower milk production and weight gain occurs. Dual-purpose operations seeking to maximize milk and beef production in the dry season can produce and feed hay or silage to their livestock.